Energy optimization strategy for integrated energy system considering energy storage thermal inertia - Li WANG; Dongwen CHEN; Junge LI; Shunqi ZENG; Yong LI (Dianxin kexue)
The advantages of multi energy conversion and coordination energy supply in the integrated energy system and the thermal inertia characteristics of the cold storage/thermal system were considered to realize the rapid recovery of energy supply system when the energy supply system fails.The power relationship of multi energy flow in all kinds of energy conversion equipment was studied.The import power of all kinds of energy conversion equipment was controlled to achieve cooperative operation.The dynamic response time of all kinds of energy conversion equipment and the method of energy storage capacity adjustment with thermal inertia of heat storage and heat storage equipment was analyzed.The dynamic response time were used as the target to optimize the running strategy,and the priority of energy supply and the optimal matching of power supply were realized when the multi energy conversion equipment fails,and the final optimal operation strategy was obtained.The example shows that the resilience of multi energy coordination and energy storage capacity can quickly deal with the energy supply failures in various scenes,realize energy supply extension at the hour level,and realize fast energy supply recovery in the energy supply system for integrated energy systems.